Epidemiological aspects of tuberculosis in Correntes-PE, Brazil (Brazilian Journal of Health Research, 2023)
Introduction: Tuberculosis is a chronic infectious disease caused by Mycobacterium tuberculosis.Objective: Describe the clinical and epidemiological profile of the disease among cases reportedto the Municipal Health Department of Correntes-PE, Brazil, from 2001 to 2018. Methods: Datawere collected from tuberculosis notification/investigation forms stored in the Disease InformationSystem of Notification (SINAN, acronym in Portuguese). Results: There was a predominance of thedisease in males (51.10%), aged between 20 and 39 years (43.10%) and incomplete primary education(53.0%). The incidence was 13.10 cases per 100,000 inhabitants in the period evaluated. Regarding theclinical aspects, 93.33% of the patients had pulmonary tuberculosis. Among these, smear microscopywas performed in 57.14%, where 39.68% had a positive result. As for the evolution of cases, the percentageof cure was 55.50%, below the goal recommended by the Brazilian Ministry of Health and thepercentage of treatment abandonment corresponded to 11.10%. Conclusion: The results of this studymade it possible to understand the epidemiological aspects of tuberculosis in the population studied,in addition to indirectly assessing the health service involved in tuberculosis control in Correntes-PE,contributing to decision-making under the Tuberculosis Control Program.
Keywords: Tuberculosis; Health Information Systems; Epidemiology